Movers or stayers? Understanding the drivers of IDP camp decongestion during post-conflict recovery in Uganda - Carlos Bozzoli; Tilman Brück; Tony Muhumuza (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
The paper explores factors that influence the household decision to leave internal displacement camps in the immediate aftermath of violent conflict. Our analysis is based on two sources of information: household survey data collected in northern Uganda for households that were displaced by the civil conflict, and geo-referenced data on armed conflict events, with which we construct our developed index of recent conflict exposure. We compare households that moved out of camps with those that remained in the camps after the region was declared safe from rebel incursions. The study covers the first few months of the end of conflict, when return was regarded as largely voluntary. We find that a history of conflict both at the place of residence, and at the expected place of return reduces the likelihood of return. Access to camp services overall encourages households to stay in camps, although the effect varies with the proportion of young household members. Results also show that a history of economic skills poses varying effects on return decisions. While experience in cultivation is associated with a high likelihood of moving out of the camp, households with members with recent experience in trading are less inclined to return. From a policy perspective, the results point to the need for recovery initiatives to ensure access to adequate infrastructures in return locations in order to fast-track reintegration.
Keywords: D74; J60; R23; 330; Conflict; IDP; Northern Uganda; returnees